Alta costura nacional: Rui Spohr, um ícone da moda gaúcha (ModaPalavra e-periódico, 2009)
This article reviews the haute couture, the concept and definitions. Through literature search and evidence, we analyzed the trajectory of life and work of designer gaucho Rui Spohr. We highlight the approaches and distance to their production style keeps / kept with the concept of haute couture
Keywords: haute couture; Rui Spohr; gaúcha fashion